A self-healing flexible transparent conductor made of copper nanowires and polyurethane. (June 2017) - Zhang, Xiaoyun; Tang, Zhou; Tian, Di; Liu, Kongyi; Wu, Wei
Graphical abstract: Highlights: Self-healing flexible conductor comprises copper nanowire and polyurethane sheath. The nanocomposite conductor exhibits a sheet resistance of 22.3 Ω sq −1 . Healing behavior can be repeated 5 times without significant loss of conductivity. The nanocomposite conductor sustains large-strain deformation. Abstract: A self-healing flexible transparent conductor comprising a core-shell copper nanowire network and healable polyurethane sheath was developed. The polyurethane pre-polymer containing furan rings was cross-linked with N, N ′-(4, 4′-methylenediphenyl) dimaleimide via a Diels-Alder reaction to form the healable network polymer. This thin polymer layer solders the copper nanowires and confines the nanowire network on the substrate surface. The nanocomposite conductor exhibits a sheet resistance of 22.3 Ω sq −1 with 66.5% transmittance at 550 nm. 98% of the surface conductivity can be recovered in 3 min at 120 °C, and the damaging-healing behavior could be repeated 5 times at the same position. The present work provides a simple way to fabricate advanced flexible transparent conductors.